Unraveling the discrepancies between REDUCE-IT and STRENGTH trials with omega-3 fatty acids: new analytical approaches - Zhang, Weiguo; Gan, Dan; Huo, Shaofeng; Chen, Peng (Frontiers in Nutrition, 2024)
Two large-scale, randomized, double-blind, placebo-controlled trials—REDUCE-IT and STRENGTH—have garnered significant attention in cardiovascular medicine. Both trials aimed to evaluate the effects of prolonged administration of nutritional lipids, specifically omega-3 fatty acids, on major adverse cardiovascular events (MACEs) in high-risk patients undergoing statin therapy. REDUCE-IT used eicosapentaenoic acid (EPA) ethyl ester with mineral oil as a control, while STRENGTH utilized a carboxylic acid formulation of both EPA and docosahexaenoic acid (DHA) with corn oil as a control. Notably, REDUCE-IT demonstrated a reduction in MACE risk with EPA, whereas STRENGTH showed no such benefit with the combination of EPA and DHA. Despite extensive and insightful discussions following the publication of these trials, the underlying reasons for this discrepancy remain elusive. We posit that further investigation into resting heart rate (RHR), heart rate variability (HRV), and ethnic subgroup data—collected but not fully explored—is critical to unraveling the divergent outcomes of the REDUCE-IT and STRENGTH trials. These additional analyses could provide pivotal insights into the mechanisms driving the differential effects of omega-3 fatty acids in high-risk cardiovascular patients. Given that previous discussions have not fully addressed these potential variables, exploring them may illuminate unexplored pathways and offer a deeper understanding of the mechanistic and clinical roles of omega-3 s in cardiovascular health. We hypothesize that by delving into these under-analyzed factors, we can not only clarify the discrepancies between the trials but also advance our broader understanding of cardiovascular nutrition and medicine.